Selected Indicators for Evaluating the Effectiveness of Marketing Communication - Olejniczak Aneta; Tomorad Darko (Marketing of Scientific and Research Organizations, 2015)
The issue of the evaluation of marketing activity in each institution most often refers to marketing communications and therefore promotional activities of the company. Whereas measuring the effectiveness of marketing communications results, we can use many tools-indicators, the use of which will track the progress and assess the effectiveness of institution run by marketing communications. With a view to implementing effective marketing strategy we must be able to measure our success. In this article, has been made a review of selected indicators to evaluate the effectiveness of marketing communications. Cited indicators are commonly used. According to the authors, each institution should create its own set of indicators by which the effects of its operations will be best measured.